2009
DOI: 10.1007/s11606-009-0924-x
|View full text |Cite
|
Sign up to set email alerts
|

Can Improved Prescription Medication Labeling Influence Adherence to Chronic Medications? An Evaluation of the Target Pharmacy Label

Abstract: BACKGROUND: Prescription medication labels contain valuable health information, and better labels may enhance patient adherence to chronic medications. A new prescription medication labeling system was implemented by Target pharmacies in May 2005 and aimed to improve readability and understanding. OBJECTIVE:We evaluated whether the new Target label influenced patient medication adherence. DESIGN AND PATIENTS:Using claims from two large health plans, we identified patients with one of nine chronic diseases who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Recently, two articles have been published on the impact of better labeling (Target ClearRx Ò labels) on adherence and rate of outpatient and inpatient health services use and emergency room visits. Although both studies had limitations such as exclusion of elderly, uninsured and beneficiaries of Medicaid in their sample study, overall, neither study demonstrated a significant impact of labels on adherence or outcomes [28,29]. Other studies including vulnerable groups of patients and differing levels of health literacy should be performed to confirm these results.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, two articles have been published on the impact of better labeling (Target ClearRx Ò labels) on adherence and rate of outpatient and inpatient health services use and emergency room visits. Although both studies had limitations such as exclusion of elderly, uninsured and beneficiaries of Medicaid in their sample study, overall, neither study demonstrated a significant impact of labels on adherence or outcomes [28,29]. Other studies including vulnerable groups of patients and differing levels of health literacy should be performed to confirm these results.…”
Section: Discussionmentioning
confidence: 90%
“…Also, determining preference may not necessarily correspond to usefulness in practice but it provides an indirect examination of usefulness because if the stakeholders prefer a label, it is more likely to be useful to them. We would like to restate the caveat, that while there may be evidence that misunderstanding labels could lead to poor patient outcomes, there is no current evidence that improving labels will lead to better outcomes [9,28,29]. Given that California is poised to move to a standardized, user-friendly label, the extension of the current research appears imperative.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier evaluation of changes to a prescription drug container and labeling did not find benefits to adherence or health outcomes. 32,33 While we cannot isolate the independent benefits of the various label changes made with the PCL, the UMS is one new, evidence-based labeling component not included in the prior mentioned research investigations. To the best of our knowledge, this is only the second investigation to evaluate explicit changes to a prescription drug container label in actual use, and the first to include the UMS.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Extensive evaluation of the rates [4][5][6] and predictors [7][8][9][10][11][12] of nonadherence have been conducted, and numerous interventions have been implemented to improve the way patients take their medications. [13][14][15] However, an important component of taking medication has been largely overlooked until the past several years.…”
mentioning
confidence: 99%